The Tax Nucleus of Gains and Losses. - Misiewicz, Kevin M. (The Accounting Review, 1978)
ABSTRACT: Much of the complexity of our federal income tax laws is due to the intricate treatment of gains and losses upon dispositions of property. Flow charts and examples are employed here to delineate the tax nucleus of this area. They can be used to increase the comprehension of students, the efficiency and effectiveness of services provided by tax professionals, and the quality of tax decisions by lawmakers.